Virtual screening and molecular docking of Indonesian phytoconstituents as potential inhibitors of peroxisome proliferator-activated receptor gamma in polycystic ovary syndrome - Tunjungseto Arif; Iffatunnisa Fakhriyah; Pratiwi Intan Winta; Alif Azzam Muhyiddin Afrizal; Ahsan Fadhil; Santoso Budi (BIO Web of Conferences)
Polycystic ovary syndrome (PCOS) is the most common endocrinology disorder affecting women of reproductive age, characterized by irregular menstruation, androgen overproduction and insulin resistance. Peroxisome proliferator-activated receptor-gamma (PPARG) is one of the essential modulators of ovarian steroid hormone synthesis and lipid metabolism. Precision medicine and targeted therapy have emerged as practical therapeutic approaches, focusing on specific molecules/pathways to minimize side effects and improve outcomes. This study aimed to identify potential Indonesian phytoconstituents that inhibit PPARG both from a pharmacokinetic and pharmacodynamic perspective based on the in silico approach. Data of 6776 phytoconstituents from the Indonesian Medicinal Plant Database were screened for compounds with Pa>0.3 as “Insulin Sensitivity”, “Lipid metabolism”, and “Anti-inflammation” using PASSOnline. We performed pharmacokinetic profile prediction using SwissADME based on Lipinski criteria. Molecular docking was carried out with PPARG as the target proteins, utilizing PyMol, Pyrx, and Discovery Studio to evaluate top-hit compounds with the highest binding affinity. Through in silico screening and molecular docking, Quercitol exhibited superior binding with the protein target compared to the control ligands and metformin. Quercitol also met the Lipinski criteria, showing favourable bioavailability as a drug candidate. Hence, these findings will provide a theoretical basis for further studies as regards drugs targeting PPARG in PCOS.